Simultaneous Preconcentration and Determination of Ni and Pb in Water Samples by Solid-Phase Extraction and Flame Atomic Absorption Spectrometry - Ciftci, Harun; Temuz, Mehmet Mursit; Ciftci, Esen (Aoac Int, 2013)
An analytical method for the preconcentration of nickel (Ni) and lead (Pb) in water samples on polystyrene-graft-ethylmethacrylate copolymer resin has been developed. The determinations of metal ions were performed by flame atomic absorption spectrometry. The experimental parameters, such as solution pH, sample flow rate, type and concentration of eluent, and amount of resin, were optimized for the preconcentration and recovery of Ni and Pb ions. Adsorbed ions on the resin were eluted by 6 mL of 2 M HNO3. Under optimized conditions, the LOD was found to be 0.92 and 1.44 mu g/L for Ni and Pb ions, respectively. The accuracy of the proposed procedure was tested by recovery studies and analysis of a standard reference material (GBW 08301, river sediment). The method was successfully applied to water samples.
Keywords: Nickel; 8-Hydroxyquinoline; Separation; Manganese; Lead(Ii); Cd(Ii); Cobalt; Column; Ions; Acid